EFEKTIVITAS PENGAWASAN DAN PENERTIBAN REKLAME DI KOTA KUPANG - Christian Lucky Bati Lidda; Laurensius P. Sayrani; Ardy Yosafat Pandie (PT. Hasba Edukasi Mandiri, 2025)
This study analyzes the effectiveness of billboard supervision and control in Kupang City within the context of optimizing Local Own-Source Revenue (Pendapatan Asli Daerah/PAD). The main issues addressed are the consistently unmet targets for billboard tax realization and the proliferation of illegal billboards lacking permits or unpaid taxes, which reduce potential local revenue and disrupt the city's aesthetics. The research employs a descriptive qualitative method, focusing on two main problems: the effectiveness of supervision in investigating billboards without tax payment and the effectiveness of enforcing Local Regulations (Peraturan Daerah/Perda) related to billboard control. The research locations include the Local Revenue Agency (Bapenda) and the Civil Service Police Unit (Satpol PP) of Kupang City, as well as several billboard management companies. The results indicate that the effectiveness of supervision in billboard tax investigation is not yet optimal. Although the V-Tax digital system has been implemented for real-time supervision, its effectiveness is limited because the system cannot detect incidental billboards or those installed without formal licensing. Furthermore, quarterly manual supervision is insufficient to keep pace with the rapid installation cycle of temporary billboards. Other constraints include limited human resources (HR) since one team must handle various tax objects, low taxpayer compliance, and suboptimal coordination among agencies such as Bapenda, the Licensing Department, and PUPR (Public Works and Housing Department), which results in slow procedures and creates opportunities for illegal billboard practices. This irregularity creates a perception of unfairness among compliant taxpayers. The study recommends strengthening inter-agency coordination, enhancing the socialization of the V-Tax system, and enforcing stricter sanctions to boost PAD and improve city planning.